2020
DOI: 10.1186/s12940-020-00625-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between the seasonality of pediatric pandemic influenza virus outbreak and ambient meteorological factors in Shanghai

Abstract: Background and objectives: The number of pediatric patients diagnosed with influenza types A and B is increasing annually, especially in temperate regions such as Shanghai (China). The onset of pandemic influenza viruses might be attributed to various ambient meteorological factors including temperature, relative humidity (Rh), and PM 1 concentrations, etc. The study aims to explore the correlation between the seasonality of pandemic influenza and these factors. Methods: We recruited pediatric patients aged fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Some subtropical areas span a single peak per year, in winter or spring/summer, whereas some in both summer and winter, or even last for the whole year [6][7][8][9][10]. In temperate, subtropical, and tropical regions, it has been shown that the low temperature is associated with high levels of influenza activity [11]. It has been reported that low daily temperatures of 0-5 • C significantly increase the risk of influenza incidence [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some subtropical areas span a single peak per year, in winter or spring/summer, whereas some in both summer and winter, or even last for the whole year [6][7][8][9][10]. In temperate, subtropical, and tropical regions, it has been shown that the low temperature is associated with high levels of influenza activity [11]. It has been reported that low daily temperatures of 0-5 • C significantly increase the risk of influenza incidence [12].…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal epidemics of the in uenza virus are well documented, with in uenza virus prevalence and average temperature having a negative correlation. On the other hand, PM10 has a positive correlation with in uenza cases (Li et al 2020), and numerous other studies have reported negative correlations between temperature and the prevalence of the in uenza virus (Cao et al 2010;Xu et al 2013;Wang et al 2017). In addition, coronaviruses also show a characteristic seasonality, which occurs mostly in winter and spring, according to a study conducted in adults (Hendley et al 1972), and human coronavirus 229E in aerosol form is generally less stable at high humidity (Ijaz et al 1985).…”
Section: Discussionmentioning
confidence: 90%
“…Seasonal epidemics of the influenza virus are well documented, with influenza virus prevalence and average temperature having a negative correlation. On the other hand, PM 10 has a positive correlation with influenza cases (Li et al 2020 ), and numerous other studies have reported negative correlations between temperature and the prevalence of the influenza virus (Cao et al 2010; Xu et al 2013 ; Wang et al 2017 ). In addition, coronaviruses also show a characteristic seasonality, which occurs mostly in winter and spring, according to a study conducted in adults (Hendley et al 1972 ), and human coronavirus 229E in aerosol form is generally less stable at high humidity (Ijaz et al 1985 ).…”
Section: Discussionmentioning
confidence: 99%